Tantangan dan Adaptasi Pendampingan Digitalisasi UMKM dalam Upaya Penguatan Branding pada UMKM Dapur Bu Milah di Kota Surabaya - Neysa Asmarani Hanindia Putri; Gwyneth Edinta; Tjokorda Istri Putri Nisya Indira; Kayla Nawra Darmawan; Aliefiradine Zalikha Murtono; Aulia Sabrina Anwar; Fatin Furoidah Ramadani; Tri Siwi Agustina (Indonesia Economic Journal, 2026)
Micro, Small, and Medium Enterprises play an important role in Indonesia's economy. However, UMKM currently face various challenges in competing in the digital era. One effort that can be undertaken to enhance their competitiveness is through business digitalization and branding enhancement to increase brand awareness among consumers. This article aims to examine the development efforts of Dapur Bu Milah through the optimization of digital-based brand awareness. The methods employed include observation, interviews, and direct mentoring of the business owner to identify existing problems and formulate solutions that align with the needs of the UMKM. The results of the program indicate that Dapur Bu Milah has strong business potential but still faces several challenges, including the underutilization of social media, limited use of digital platforms, and a weak brand identity. Therefore, several mentoring programs were implemented, including the creation of a new logo, the updating of QRIS payment facilities, the establishment of social media accounts, and assistance with registration for GrabFood services. These initiatives are expected to increase the business's visibility, strengthen its brand identity, expand its market reach, and improve its competitiveness in the digital era. Thus, digitalization and branding enhancement are essential strategies for supporting the sustainable development of UMKM..